2021
DOI: 10.5194/acp-21-9151-2021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of weather situation on non-CO<sub>2</sub> aviation climate effects: the REACT4C climate change functions

Abstract: Abstract. Emissions of aviation include CO2, H2O, NOx, sulfur oxides, and soot. Many studies have investigated the annual mean climate impact of aviation emissions. While CO2 has a long atmospheric residence time and is almost uniformly distributed in the atmosphere, non-CO2 gases and particles and their products have short atmospheric residence times and are heterogeneously distributed. The climate impact of non-CO2 aviation emissions is known to vary with different meteorological background situations. The a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 71 publications
14
45
0
Order By: Relevance
“…America, C2 is the most commonly occurring trajectory type (50%) and also displays the fastest descent at 23.6 hPa•day -1 followed by an increase in altitude. Trajectories C1 -C3 for S. America continue to support the tendency highlighted by Frömming et al (2021) and Rosanka et al (2020), namely that a faster initial descent will yield larger O3 maxima until being washed out after reaching the minimum in altitude. For Eurasia, all trajectories exhibit similar vertical profiles with relatively low rates of descent when compared to C2 in Eurasia during January -March 2014.…”
Section: Profiles For July 2014supporting
confidence: 58%
See 3 more Smart Citations
“…America, C2 is the most commonly occurring trajectory type (50%) and also displays the fastest descent at 23.6 hPa•day -1 followed by an increase in altitude. Trajectories C1 -C3 for S. America continue to support the tendency highlighted by Frömming et al (2021) and Rosanka et al (2020), namely that a faster initial descent will yield larger O3 maxima until being washed out after reaching the minimum in altitude. For Eurasia, all trajectories exhibit similar vertical profiles with relatively low rates of descent when compared to C2 in Eurasia during January -March 2014.…”
Section: Profiles For July 2014supporting
confidence: 58%
“…The mixing itself between Lagrangian parcels depends on dimensionless mixing coefficients defined per vertical layer (e.g., the troposphere) and is parameterized via the LGTMIX (LaGrangian Tracer MIXing) sub-model (Brinkop and Jöckel, 2019). Along each of these air parcel trajectory points, the AIRTRAC sub-model then calculates the contribution of the NOx emissions to the atmospheric composition of O3, CH4, HNO3, OH and active nitrogen species (NOy) by also Sander et al, 2011) for the troposphere and stratosphere, as is described by Frömming et al (2021) and Rosanka et al (2020). The effect of a NOx disturbance on the mixing ratios of other chemical species like O3 can be understood in terms of an interaction between production and loss terms in which O3 production is initiated by the reaction 𝑁𝑂 + 𝐻𝑂 2 → 𝑂𝐻 + 𝑁𝑂 2 , followed by the photolysis of NO2 (𝑁𝑂 2 + ℎ𝑣 → 𝑁𝑂 + 𝑂) and finally the combination of oxygen and dioxygen (𝑂 + 𝑂 2 → 𝑂 3 ).…”
Section: The Emac Model and Relevant Sub-modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee et al, 2010) and aviation-induced radiative forcing (RF) (as reported by Lee et al, 2009 and adapted by Grewe, Dahlmann, et al, 2017) Emissions of NO x affect the climate indirectly by an increase in ozone concentration (O 3 ; warming effect of 26.3 mW/m 2 ) and a reduction in methane concentration (CH 4 ; cooling effect of −15.4 mW/m 2 ; Grewe et al, 2019), which are both important greenhouse gases. The level of the positive net NO x effect, however, varies greatly with the emission location in terms of altitude (Grewe & Stenke, 2008), geographic region (Köhler et al, 2013;Stevenson & Derwent, 2009), and time of the year (Hoor et al, 2009;Søvde et al, 2014), with the consequence that NO x emissions can even cause a cooling effect in certain regions (Frömming et al, 2021). The largest individual contribution to the total RF of aviation is currently attributed to contrail cirrus (CC), whereas for the induced temperature change the three components CO 2 , NO x , and CC might be about equally important (Grewe, 2020;Ponater & Bickel, 2020).…”
Section: Introductionmentioning
confidence: 99%